Internal ribosome entry site for expression of infectious bursal disease viral segments A and B genes in Arabidopsis thaliana (L.) Heynh - Liew, Pit Sze (2015)
Infectious bursal disease (IBD) is an acute and highly contagious viral infection of young chickens caused by the IBD virus (IBDV). The IBDV genome consists of two segments: A and B. Segment A has two partially overlapping open reading frames that encode for viral protein VP5 and precursor polyprotein. The precursor polyprotein undergoes proteolytic cleavage to give rise to mature viral proteins VP2, VP3 and VP4. The genome segment B encodes for viral protein VP1. A growing body of evidence showed that both genome segments of IBDV contribute to the virulence and pathogenicity of the virus. As the principal control method of IBDV infection in chickens is by vaccination, the application of whole IBDV genome involving both segments A and B for vaccination become judicious and crucial. The present study was therefore undertaken to determine the feasibility of expressing both IBDV genome segments A and B of a local virus isolate in the plant production system, as part of the greater goal in development of effective poultry vaccines. Since plants offer several distinct advantages over other systems, expression of IBDV viral proteins from both genome segments were thus carried out in the chosen host plant Arabidopsis thaliana or commonly known as thale cress, mouse-ear cress or arabidopsis by Agrobacterium-mediated transformation. At the same time, internal ribosome entry site (IRES) from tobacco etch virus (TEV) and crucifer-infecting tobamovirus (CrTMV) capable of initiating translation internally of an mRNA transcript were selected to determine their usefulness in expression of IBDV genes. Prior to expression in the plant, complete nucleotide (nt) coding sequence of the UPM04/190 IBDV isolate was determined. In segment A, there were 465 nt with 154 amino acids (aa) in VP5, while the polyprotein contained 3039 nt with 1012 aa. In segment B, there were 2640 nt with 879 aa in VP1. In comparison with the published sequences on the deduced aa, it revealed nine unique aa conserved only in UPM04/190 IBDV. They were D240G, E677K, and L693H in VP1, D212N, Q249E and I264M in hypervariable region of VP2, and V616I in VP4. The VP5 has two unique substitutions at L133I and position 150 from a stop codon to arginine that led to the extension of its C-terminal. There were no unique aa substitutions found in VP3. The overall branching pattern of the phylogenetic trees clustered the UPM04/190 IBDV with very virulent IBDV. Following molecular characterisation, UPM04/190 IBDV isolate was used to construct expression plasmids. The genome segments A and B were linked by CrTMV or TEV IRES, and inserted into a plasmid vector pcDNA™-DEST40 via recombinational cloning to make an expression clone compatible for expression in wheat germ extract. In vitro transcription produced ssRNA runoff transcripts of appropriate sizes upon separation on resolving gel. Protein expression in wheat germ extract has also verified the presence of specific protein size. The presence of VP4 protein or smaller form of VP3 protein led to the assumption that the polyprotein has been transcribed and expressed from the expression clones. In the IRES-containing expression clones, the presence of VP1 protein revealed that the IRES were functional in wheat germ extracts. Following this, plant transformation plasmids were constructed. The genes of interest were transferred into the T-DNA region of a binary plant destination vector pMDC32, after which were mobilised into Agrobacterium tumefaciens strain LBA4404. Transient infection to validate the expression of IBDV viral proteins was achieved in 5-day-old Arabidopsis thaliana seedlings by co-cultivation with Agrobacterium colonies carrying constructs of interest. After co-cultivation, RT-PCR specific for IBDV VP1 and VP4 genes were performed on the total plant RNA extract and detected products of expected band size upon agarose gel electrophoresis. Western blot analysis on the transiently expressed IBDV proteins also saw the expression of IBDV-specific proteins. Following transient expression assay, the same plant transformation plasmids were used for stable transformation of A. thaliana adult plants. Seeds from the treated T0 generation plants were grown on selection media to screen for positive primary transformants. The positive T1 plants were then pushed through T2 generation to obtain T3 seeds. Preliminary PCR screening targeting the HPT gene within T-DNA region had identified five transgene positive plants. Further PCR identification targeting both partial and full-length IBDV gene specific sequences have revealed two plants that were positive for segment A-specific genes and another two plants were positive for segment B-specific genes. The remaining one plant transformed with plasmid containing both IBDV segments linked by the CrTMV IRES was positive for both segments A- and B-specific genes. Hybridisation with polyclonal IBDV antibodies had detected the mature VP2 protein in segment A-containing plants, while hybridisation with VP1 antibodies have also found the VP1 protein in segment B-containing plants. In conclusion, the present study demonstrated the importance of using both segments A and B for characterisation of IBDV strains, especially the very virulent IBDV due to their co-operative manners in affecting the viral virulence and pathogenicity. The study revealed that plants, specifically Arabidopsis thaliana, were capable of supporting the processing of polyprotein and maturation of IBDV precursor VP2 protein. The IRES were also functional in Arabidopsis and promoted translation of downstream VP1 gene when placed in a distal cistron in a dicistronic construct. The use of IRES for gene expression in plant production system is warranted for further exploration for vaccine development, applicable not only for IBDV, but also many pathogenic agents of importance in poultry.